Improving Antibiotic De-Escalation in Suspected Ventilator-Associated Pneumonia: An Observational Study With a Pharmacist-Driven Intervention. (October 2015) - Oxman, David A.; Adams, Christopher D.; Deluke, Gretchen; Philbrook, Lauren; Ireland, Peter; Mitani, Aya; Panizales, Christia; Frendl, Gyorgy; Rogers, Selwyn O.
Background: Recommendations for treatment of ventilator-associated pneumonia (VAP) emphasize early empiric broad-spectrum antibiotics. However, appropriate antibiotic de-escalation is also critical for optimal patient care. Materials and Methods: We examined how often intensivists in our institution appropriately de-escalated antibiotics in cases of suspected VAP, and whether decision support by intensive care unit pharmacists could improve rates of antibiotic targeting and early antibiotic discontinuation in low-risk patients. Main Results: A total of 92 (observation phase = 50; intervention phase = 42) patients with suspected VAP were identified. During the observation phase, 39 cases yielded positive sputum cultures, but in only 23 (59%) were antibiotics targeted to culture results. This rate improved during the intervention phase when 29 (91%) of 32 cases with positive cultures were targeted ( P value .003). There were 48 cases in which the risk of pneumonia was considered low. Of the 26 low-risk cases in the observation phase, 5 (19%) had antibiotics discontinued early versus 5 (23%) of the 22 cases in the intervention phase. Conclusions: Decision support by clinical pharmacists significantly improved rates of appropriate antibiotic targeting in cases of culture-positive suspected VAP but did not have a significant effect on early antibiotic discontinuation in patients at low risk of true pneumonia.